2017
DOI: 10.1002/ana.25065
|View full text |Cite
|
Sign up to set email alerts
|

Pooled analysis of the HLA‐DRB1 by smoking interaction in Parkinson disease

Abstract: Objective Inflammatory response plays an important role in Parkinson’s disease (PD). Previous studies have reported an association between human leukocyte antigen (HLA)-DRB1 and the risk of PD. There has also been growing interest in investigating whether inflammation-related genes interact with environmental factors such as smoking to influence PD risk. We performed a pooled analysis of the interaction between HLA-DRB1 and smoking in PD in three population-based case-control studies from Denmark and France. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 44 publications
4
23
0
Order By: Relevance
“…2 Other epidemiologic studies suggested significant gene-by-smoking interaction effects in PD. 47,48 In our study, we observed a PD risk reduction of 31% for ever smokers vs never smokers. Although risk reduction effects demonstrated in an observational study and in an MR study may not be comparable, a consistency in the direction of protective associations by both the approaches is an important finding.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…2 Other epidemiologic studies suggested significant gene-by-smoking interaction effects in PD. 47,48 In our study, we observed a PD risk reduction of 31% for ever smokers vs never smokers. Although risk reduction effects demonstrated in an observational study and in an MR study may not be comparable, a consistency in the direction of protective associations by both the approaches is an important finding.…”
Section: Discussionsupporting
confidence: 46%
“…The identified associated phenotypes were then investigated for association with PD through a thorough literature search. Using this strategy, we identified rheumatoid arthritis, years of educational attainment, adiposity-related traits, age at menarche, and type 1 diabetes mellitus as potential confounders [45][46][47][48][49] (figure 2). We identified 8 genetic variants or loci from our genetic instrument for the tendency to smoke phenotype associated with different confounding traits.…”
Section: Genetic Variants Associated With Potential Confoundersmentioning
confidence: 99%
“…A meta-analysis merging smoking status trait from 33 different populations demonstrated a risk reduction by 36% for ever-vs never-smokers with consistent results in both case-control and cohort studies 2 . Other epidemiological studies suggested significant gene-by-smoking interaction effects in PD 46, 47 . In our study, we observed a PD risk reduction of 31% for ever smokers vs never smokers.…”
Section: Discussionmentioning
confidence: 92%
“…In rheumatoid arthritis, the risk of developing antibodies to citrullinated proteins has been associated with gene–environment interactions between HLA‐DRB1 shared epitope alleles and smoking . Other diseases showing associations between HLA and smoking include idiopathic inflammatory myopathies, Parkinson disease, multiple sclerosis, and lymphoma …”
Section: Discussionmentioning
confidence: 99%
“…30 In rheumatoid arthritis, the risk of developing antibodies to citrullinated proteins has been associated with gene-environment interactions between HLA-DRB1 shared epitope alleles and smoking. [30][31][32][33][34] Other diseases showing associations between HLA and smoking include idiopathic inflammatory myopathies, 35 Parkinson disease, 36,37 multiple sclerosis, [38][39][40][41] and lymphoma. 42 In the current study, the strong effects of HLA-DRB1*15:02 on the risk of UC were observed in never smokers.…”
Section: Discussionmentioning
confidence: 99%